ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN TAMU DALAM PERJALAN HAJI DAN UMROH DI HASUNA TOUR HAJJ AND UMRAH SERVICES YOGYAKARTA - , FARIKHA RATNA D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This Research aims to find out if the dimensions in service quality there are tangible, reliability, responsiveness, assurance, and empathy to guest satisfaction at the Hasuna Tour Hajj and Umroh Services and analyze the dominant factors that impact customer satisfaction Hasuna Tour guests. This thesis is presented in qualitative and quantitative to get an overview of various informastion related to the influence of the quality of service to guests satisfaction. Method of data collection that is used for library studies with writers, interviews, observation, and data analysis. The data obtained are then analyzed qualitatively and presented in a descriptive. The results showed that Hasuna Tour has quality services in the category of good. It appears from the answers of the respondentd to the questionnaire submitted statements as well as from other observations wich show agreement on the good services of physical appearance, reliability serve guests, responsiveness, assurance, and concern for the guests. The quality perceived by consumers provide of a good service quality in the provision of services, grow a satisfaction for consumers.